О полной динамической структуре электромагнитного вибровозбудителя - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
The dynamical equations for the mechanical, magnetic, and electric parts of an electromagnetic vibroexciter are given. The full dynamical structural scheme of its dynamical state is presented.